History, Variations, and Extensions of the Retrosigmoid Approach: Anatomical and Literature Review - Basma, Jaafar; Anagnostopoulos, Christos; Tudose, Andrei; Harty, Mikhail; Michael, L. Madison, II; Teo, Mario; Porter, David G. (Journal of Neurological Surgery Part B: Skull Base, 2021)
The retrosigmoid approach is the workhorse for posterior fossa surgery. It gives a versatile corridor to tackle different types of lesions in and around the cerebellopontine angle. The term “extended” has been used interchangeably in the literature, sometimes creating confusion. Our aim was to present a thorough analysis of the approach, its history, and its potential extensions. Releasing cerebrospinal fluid from the subarachnoid spaces and meticulous microsurgical techniques allowed for the emergence of the retrosigmoid approach as a unilateral variation of the traditional suboccipital approach. Anatomical landmarks are helpful in localizing the venous sinuses and planning the craniotomy, and Rhoton's rule of three is the key to unlock difficult neurovascular relationships. Extensions of the approach include, among others, the transmastoid, supracerebellar, far-lateral, jugular foramen, and perimeatal approaches. The retrosigmoid approach applies to a broad range of pathologies and, with its extensions, can provide adequate exposure, obviating the need for extensive and complicated approaches.
Keywords: retrosigmoid approach; posterior fossa; history; neuroanatomy; craniotomy